Effects of Dual Initial Combination Therapy With Macitentan Plus Riociguat or Macitentan Plus Selexipag on Hemodynamics in Patients With Pulmonary Arterial Hypertension (SETOUCHI-PH Study) ― Protocol of a Multicenter Randomized Control Trial ― - Akagi, Satoshi (Circ Rep, 2021)
Background: The latest guideline from the European Society of Cardiology and European Respiratory Society recommends initial combination therapy with oral pulmonary arterial hypertension (PAH)-specific drugs in PAH patients with World Health Organization functional class (WHO-FC) II or III. However, whether this initial combination therapy improves hemodynamics and clinical failure events regardless of the combination of PAH-specific drugs remains unknown. This study was designed to evaluate whether the initial combination therapy with macitentan plus riociguat or macitentan plus selexipag showed equal efficacy in reducing pulmonary vascular resistance (PVR) 8 months after administration. Methods and Results: This study is a multicenter randomized control trial. PAH subjects with WHO-FC II or III will be randomized (1 : 1) into initial combination therapy with either macitentan plus riociguat or macitentan plus selexipag, and will be observed 8 months after the initiation of treatment. The primary endpoint will be the difference in the change ratio of PVR from baseline to after 8 months of treatment. Conclusions: The SETOUCHI-PH study will clarify whether initial combination therapy with macitentan plus riociguat or macitentan plus selexipag results in equal reductions in PVR 8 months after administration.